Potassium ion half cell and preparation method thereof

By synthesizing CN-COF materials with high conductivity and stable frame structure and assembling with bisfluorosulfonimide potassium salt-based electrolyte, the problem of poor conductivity of existing potassium ion battery negative electrode materials is solved, and high capacity is achieved. Improved stability and rate performance while reducing energy consumption.

CN119419366APending Publication Date: 2025-02-11ZHENJIANG MEASUREMENT VERIFICATION TEST CENT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411548855.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The COF, the negative electrode material of the existing potassium ion battery, has poor conductivity, resulting in low capacity and poor rate performance. The preparation process requires high temperature processing and high energy consumption.

Method used

CN-COF material is synthesized by heating the raw materials such as 1,2,4,5-tetraaminobenzene, cyclohexanone octahydrate and N-methylpyrrolidone through concentrated sulfuric acid oil bath, and electrolyzed with bisfluorosulfonimide potassium salt-based The liquid is assembled into a potassium half-cell.

Benefits of technology

The potassium storage capacity, cycle stability and rate performance of potassium ion half-cell are improved, the energy consumption of synthesis is reduced, and high-temperature treatment steps are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419366A_ABST
    Figure CN119419366A_ABST
Patent Text Reader

Abstract

The invention discloses a potassium ion half-cell and a preparation method thereof, the potassium ion half-cell comprises a potassium metal, a CN-COF material and an electrolyte, the CN-COF material is prepared by performing oil bath heating synthesis on 1, 2, 4, 5-tetraaminobenzene, cyclohexanone octahydrate, N-methyl pyrrolidone and concentrated sulfuric acid, purifying and then freeze-drying; and the electrolyte is a bis (fluorosulfonyl) imide potassium salt-based electrolyte. The preparation method comprises the following steps: preparing a CN-COF material; the preparation method comprises the following steps: fully dissolving bis (fluorosulfonyl) imide potassium salt and a solvent in a protective atmosphere to obtain an electrolyte; and assembling the CN-COF material, an electrolyte and potassium metal into the potassium ion half-cell. In the aspect of an energy storage system, the method is not limited to material design, the matching property of the material and the electrolyte is considered, a CN-COF / 3M KFSI-THF new system with highly matched electrode material / electrolyte is provided, and the potassium storage capacity and the cycling stability of the material are synchronously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a battery and a preparation method thereof, in particular to a potassium ion half-battery and a preparation method thereof. Background Art

[0002] Organic anodes have attracted increasing attention due to their advantages such as high selectivity, high theoretical capacity, and designable structure. Among them, COF is a polymer with a designed periodic skeleton and ordered nanopores. COF with controllable pore size and redox centers has been shown to be useful for electrochemical energy storage and conversion. In order to apply more efficient electrodes, the COF skeleton can contain active groups such as C=N bonds, where the N site can be used as a K storage site. In addition, the pore channels of COF materials should be large enough to accommodate K + It can hold large ions without volume expansion, thus facilitating ion transport.

[0003] At present, researchers have prepared COF materials for the negative electrode of potassium ion batteries. Due to the poor conductivity of the synthesized materials, there are problems such as low capacity and poor rate performance. The preparation requires high-temperature treatment and high synthesis energy consumption. Summary of the invention

[0004] Purpose of the invention: In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a potassium ion half-cell with good potassium storage capacity, good cycle stability and the ability to be used under extreme conditions such as high rates. Another purpose of the present invention is to provide a method for preparing a potassium ion half-cell with a simple synthesis process and low energy consumption.

[0005] Technical solution: The potassium ion half-cell described in the present invention includes potassium metal, CN-COF material, and electrolyte. The CN-COF material is synthesized by heating 1,2,4,5-tetraaminobenzene, cyclohexanone octahydrate, N-methylpyrrolidone (NMP), and concentrated sulfuric acid in an oil bath, purified, and then freeze-dried; the electrolyte is a potassium bis(fluorosulfonyl)imide (KFSI) electrolyte.

[0006] Furthermore, the solvent of the potassium bis(fluorosulfonyl)imide salt-based electrolyte is one or more of ethylene carbonate (EC), diethyl carbonate (DEC), ethylene glycol dimethyl ether (DME), and tetrahydrofuran (THF).

[0007] Preferably, the solvent of the potassium bis(fluorosulfonyl)imide salt-based electrolyte is tetrahydrofuran.

[0008] Furthermore, the concentration of the electrolyte is 1 to 3 mol / L.

[0009] A method for preparing a potassium ion half-cell according to the present invention comprises the following steps:

[0010] Step 1: In a protective atmosphere, 1,2,4,5-tetraaminobenzene, cyclohexanone octahydrate and N-methylpyrrolidone are placed in an ice bath, concentrated sulfuric acid is added, the temperature is raised to room temperature, and then replaced with an oil bath. After the heating is completed, the mixture is cooled to room temperature and water is added. At this time, a solid product is precipitated, which is collected by filtration, purified, and freeze-dried to obtain a CN-COF material;

[0011] Step 2, under a protective atmosphere, fully dissolving bis(fluorosulfonyl)imide potassium salt and a solvent to obtain an electrolyte;

[0012] Step three, assemble the CN-COF material, electrolyte and potassium metal into a potassium ion half-cell.

[0013] Furthermore, in step 1, the mass volume ratio of 1,2,4,5-tetraaminobenzene, cyclohexanone octahydrate, and N-methylpyrrolidone is 2g:2-3g:80mL. The temperature of the oil bath is 170-180°C for 7-9h. After heating to room temperature, keep warm for 2-3h. Preferably, the temperature of the oil bath is 175°C for 8h.

[0014] Further, purification was performed by Soxhlet extraction with methanol and water.

[0015] Furthermore, in step 2, the concentration of the electrolyte is 1 to 3 mol / L. The solvent is one or more of ethylene carbonate, diethyl carbonate, ethylene glycol dimethyl ether, and tetrahydrofuran. Ion solvation / desolvation at the electrolyte interface and ion transport through SEI are very important for the rate performance and stability of the negative electrode material, so the regulation of the electrolyte is particularly important.

[0016] Furthermore, the protective atmosphere is nitrogen or argon.

[0017] Working principle: The synthesized CN-COF material contains abundant cationic N groups and conjugated systems, has a fairly stable framework structure and regular porous channels, can promote the transfer of ions and electrons, and thus has good cycle stability and rate performance. The synthesis of CN-COF materials and the electrode-electrolyte interface regulation strategy effectively enhance the specific capacity, rate performance and long cycle performance of the CN-COF negative electrode. Due to the low solvation capacity of THF solvent, a solvation structure dominated by ion aggregates (AGG) and contact ion pairs (CIP) is formed in the optimized electrolyte, which means that K + and FSI - The strong coordination ability of induced anion-derived SEI and promoted the kinetics.

[0018] Beneficial effects: Compared with the prior art, the present invention has the following significant features:

[0019] 1. In terms of energy storage system, we are not limited to material design, but consider the compatibility between materials and electrolytes. We propose a new CN-COF / 3M KFSI-THF system with highly matched electrode materials and electrolytes, which simultaneously improves the potassium storage capacity and cycle stability of the material.

[0020] 2. CN-COF materials do not require high-temperature heat treatment steps, the synthesis process is simple and the energy consumption is low;

[0021] 3. The nanopore size of CN-COF material is larger (1.22nm), which is more suitable for the storage of K+ with large ion radius and potassium ion battery application;

[0022] 4. The obtained CN-COF material exhibits a fast kinetic adsorption-intercalation composite potassium storage mechanism in a matching potassium storage system, which is conducive to its application under extreme conditions such as high rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic diagram of the synthesis of CN-COF of the present invention;

[0024] Figure 2 is a characterization diagram of CN-COF of the present invention, wherein a is an infrared spectrum, b is an XPS spectrum, c is an XRD spectrum, and d is a Raman spectrum;

[0025] Figure 3 : is a comparison diagram of the cycle performance of CN-COF of the present invention in different electrolytes, wherein a is the charge-discharge curve at a current density of 200 mA / g, and b is the corresponding rate curve;

[0026] Figure 4 The electrochemical performance of CN-COF of the present invention in 3M KFSI / THF electrolyte, wherein a is the charge-discharge curve at different cycle numbers at a current density of 50 mAg, and b is the long cycle curve at a current density of 500 mA / g;

[0027] Figure 5 This is a diagram of the potassium storage mechanism of CN-COF, where a is the electron paramagnetic resonance spectrum of CN-COF and graphite, and b is a schematic diagram of ion / electron transport and storage in the potassium storage process of CN-COF;

[0028] Figure 6 is the cycle curve in K||K battery with different electrolytes;

[0029] Figure 7 is the infrared spectrum of the electrolyte;

[0030] Figure 8 is the Raman spectrum and Raman peak separation result of the electrolyte, where a is the Raman spectrum and b is the Raman peak separation result;

[0031] Fig. 9 TOF-SIMS test of CN-COF electrode in different electrolytes - Depth distribution of , where a is 3M KFSI-THF and b is 3M KFSI-EC+DEC. DETAILED DESCRIPTION

[0032] The experimental methods described in the examples are conventional methods unless otherwise specified; the reagents and materials are commercially available unless otherwise specified.

[0033] Example 1

[0034] A method for preparing a potassium ion half-cell comprises the following steps:

[0035] S1. Preparation of CN-COF materials, such as Figure 1 As shown:

[0036] (1) In a nitrogen atmosphere, 2 g of 1,2,4,5-tetraaminobenzene, 2.25 g of cyclohexanone octahydrate and 80 mL of NMP were placed in a three-necked flask and placed in an ice bath.

[0037] (2) Add a few drops of concentrated sulfuric acid and raise the temperature of the flask to room temperature and maintain for 2 hours. Then replace the ice bath with an oil bath and heat to 175°C and maintain for 8 hours.

[0038] (3) After heating, the flask was cooled to room temperature and water was added. The solid product precipitated and was collected by filtration. The obtained dark solid was further extracted with methanol and water and then freeze-dried for 3 days to obtain CN-COF.

[0039] S2. Prepare electrolyte: In a glove box filled with Ar (water content less than 0.01 ppm, oxygen content less than 0.01 ppm), add 1 mL of ethylene carbonate and diethyl carbonate (EC+DEC) solvent to the electrolyte bottle, and then add 1 mmol of KFSI to the electrolyte bottle. After sufficient dissolution, a 1 M KFSI / EC+DEC potassium ion battery electrolyte is obtained.

[0040] S3. Assemble CN-COF material, electrolyte and potassium metal into a potassium ion half-cell.

[0041] Example 2

[0042] A method for preparing a potassium ion half-cell comprises the following steps:

[0043] S1. Preparation of CN-COF materials:

[0044] (1) In a nitrogen atmosphere, 2 g of 1,2,4,5-tetraaminobenzene, 2.25 g of cyclohexanone octahydrate and 80 mL of NMP were placed in a three-necked flask and placed in an ice bath.

[0045] (2) Add a few drops of concentrated sulfuric acid and raise the temperature of the flask to room temperature and maintain for 2 hours. Then replace the ice bath with an oil bath and heat to 175°C and maintain for 8 hours.

[0046] (3) After heating, the flask was cooled to room temperature and water was added. The solid product precipitated and was collected by filtration. The obtained dark solid was further extracted with methanol and water and then freeze-dried for 3 days to obtain CN-COF.

[0047] S2. Prepare electrolyte: In a glove box filled with Ar (water content less than 0.01 ppm, oxygen content less than 0.01 ppm), add 1 mL of EC+DEC solvent to the electrolyte bottle, and then add 3 mmol of KFSI to the electrolyte bottle. After sufficient dissolution, a potassium ion battery electrolyte of 3 M KFSI / EC+DEC is obtained.

[0048] S3. Assemble CN-COF material, electrolyte and potassium metal into a potassium ion half-cell.

[0049] Example 3

[0050] A method for preparing a potassium ion half-cell comprises the following steps:

[0051] S1. Preparation of CN-COF materials:

[0052] (1) In a nitrogen atmosphere, 2 g of 1,2,4,5-tetraaminobenzene, 2.25 g of cyclohexanone octahydrate and 80 mL of NMP were placed in a three-necked flask and placed in an ice bath.

[0053] (2) Add a few drops of concentrated sulfuric acid and raise the temperature of the flask to room temperature and maintain for 2 hours. Then replace the ice bath with an oil bath and heat to 175°C and maintain for 8 hours.

[0054] (3) After heating, the flask was cooled to room temperature and water was added. The solid product precipitated and was collected by filtration. The obtained dark solid was further extracted with methanol and water and then freeze-dried for 3 days to obtain CN-COF.

[0055] S2. Prepare electrolyte: In a glove box filled with Ar (water less than 0.01 ppm, oxygen less than 0.01 ppm), add 1 mL of ethylene glycol dimethyl ether (DME) solvent to an electrolyte bottle, then take an electrolyte bottle and add 3 mmol KFSI, and after sufficient dissolution, obtain a 3M KFSI / DME potassium ion battery electrolyte.

[0056] S3. Assemble CN-COF material, electrolyte and potassium metal into a K||K potassium ion half-cell.

[0057] Example 4

[0058] A method for preparing a potassium ion half-cell comprises the following steps:

[0059] S1. Preparation of CN-COF materials:

[0060] (1) In a nitrogen atmosphere, 2 g of 1,2,4,5-tetraaminobenzene, 2.25 g of cyclohexanone octahydrate and 80 mL of NMP were placed in a three-necked flask and placed in an ice bath.

[0061] (2) Add a few drops of concentrated sulfuric acid and raise the temperature of the flask to room temperature and maintain for 2 hours. Then replace the ice bath with an oil bath and heat to 175°C and maintain for 8 hours.

[0062] (3) After heating, the flask was cooled to room temperature and water was added. The solid product precipitated and was collected by filtration. The obtained dark solid was further extracted with methanol and water and then freeze-dried for 3 days to obtain CN-COF.

[0063] S2. Prepare electrolyte: In a glove box filled with Ar (water content less than 0.01 ppm, oxygen content less than 0.01 ppm), add 1 mL of THF solvent to the electrolyte bottle, and then add 3 mmol of KFSI to the electrolyte bottle. After sufficient dissolution, 3 M KFSI / THF potassium ion battery electrolyte is obtained.

[0064] S3. Assemble CN-COF material, electrolyte and potassium metal into a K||K potassium ion half-cell.

[0065] Example 5

[0066] A method for preparing a potassium ion half-cell comprises the following steps:

[0067] S1. Preparation of CN-COF materials:

[0068] (1) In a nitrogen atmosphere, 2 g of 1,2,4,5-tetraaminobenzene, 2 g of cyclohexanone octahydrate, and 80 mL of NMP were placed in a three-necked flask and placed in an ice bath.

[0069] (2) Add a few drops of concentrated sulfuric acid and raise the temperature of the flask to room temperature and maintain it for 3 hours. Then, replace the ice bath with an oil bath and heat it to 170°C and maintain it for 9 hours.

[0070] (3) After heating, the flask was cooled to room temperature and water was added. The solid product precipitated and was collected by filtration. The obtained dark solid was further extracted with methanol and water and then freeze-dried for 3 days to obtain CN-COF.

[0071] S2. Prepare electrolyte: In a glove box filled with Ar (water content less than 0.01 ppm, oxygen content less than 0.01 ppm), add 1 mL of THF solvent to the electrolyte bottle, and then add 3 mmol of KFSI to the electrolyte bottle. After sufficient dissolution, 3 M KFSI / THF potassium ion battery electrolyte is obtained.

[0072] S3. Assemble CN-COF material, electrolyte and potassium metal into a K||K potassium ion half-cell.

[0073] Example 6

[0074] A method for preparing a potassium ion half-cell comprises the following steps:

[0075] S1. Preparation of CN-COF materials:

[0076] (1) In a nitrogen atmosphere, 2 g of 1,2,4,5-tetraaminobenzene, 3 g of cyclohexanone octahydrate and 80 mL of NMP were placed in a three-necked flask and placed in an ice bath.

[0077] (2) Add a few drops of concentrated sulfuric acid and raise the temperature of the flask to room temperature and maintain it for 3 hours. Then, replace the ice bath with an oil bath and heat it to 180°C and maintain it for 7 hours.

[0078] (3) After heating, the flask was cooled to room temperature and water was added. The solid product precipitated and was collected by filtration. The obtained dark solid was further extracted with methanol and water and then freeze-dried for 3 days to obtain CN-COF.

[0079] S2. Prepare electrolyte: In a glove box filled with Ar (water content less than 0.01 ppm, oxygen content less than 0.01 ppm), add 1 mL of THF solvent to the electrolyte bottle, and then add 3 mmol of KFSI to the electrolyte bottle. After sufficient dissolution, 3 M KFSI / THF potassium ion battery electrolyte is obtained.

[0080] S3. Assemble CN-COF material, electrolyte and potassium metal into a K||K potassium ion half-cell.

[0081] The embodiment The resulting battery Performance characterization:

[0082] like Figure 2 As shown, the 1,2,4,5-tetraaminobenzene, cyclohexanone octahydrate, NMP and concentrated sulfuric acid of Example 4 were heated in an oil bath to obtain a CN-COF material having a fairly stable framework structure and regular porous channels with an average pore size of 1.22 nm, which can promote the storage of K+ with a large ionic radius.

[0083] like Figure 3As shown, the charge and discharge curves of CN-COF obtained in Example 4 at a current density of 200 mA / g in different electrolytes show that the capacity in 3M KFSI / THF electrolyte is the highest. In addition, in the rate performance tests at current densities of 50, 100, 200 and 500 mA / g, the discharge capacities of CN-COF in 3M KFSI / THF electrolyte are 387.7, 280.6, 240.5 and 160.3 mAh / g, respectively. When the current density returns to 50 mA / g, in 3M KFSI / THF electrolyte, the capacity can be restored to 389.4 mAh / g, while in 1M KFSI / EC+DEC, 3M KFSI / EC+DEC and 3M KFSI / DME, the capacities can only be maintained at 262.7, 310.6 and 315.6 mAh / g, respectively.

[0084] like Figure 4 As shown, at a current density of 50mA / g, the CN-COF material obtained in Example 4 was subjected to a constant current charge and discharge test, and CN-COF exhibited a high capacity of 397.8mAh / g. As the number of cycles increased, the curve overlapped better and the capacity decayed less. In addition, the CN-COF material was tested for long cycles at a high current density. CN-COF cycled 1500 times at a high current density of 500mA / g, and the capacity remained at 95.3mAh / g, and the CE remained at almost 99%, which shows that the CN-COF negative electrode has good long cycle performance at high currents.

[0085] like Figure 5 As shown, compared with conventional carbon materials (graphite), CN-COF materials can not only store potassium through intercalation, but also store potassium through ion migration through its unique three-dimensional structure. It has abundant cationic N groups, which can provide more potassium storage sites. The conjugated system forms a conductive network to accelerate electron transfer. In addition, the stable framework structure and regular porous channels shorten the ion diffusion distance and achieve fast electrochemical kinetics.

[0086] like Figure 6 As shown, under different current densities, the batteries of the four electrolytes obtained in Examples 1 to 4 cycled for 200 h. The voltage curve of the symmetric K||K battery with 3MKFSI / THF as the electrolyte was stable and the polarization was low. The metallic potassium in the K||K battery could be reversibly deposited / stripped at high current density, thereby achieving long cycles. This confirmed that the THF electrolyte had better stability from an electrochemical point of view.

[0087] like Figure 7As shown in the figure, compared with pure EC+DEC solvent, after adding KFSI, shoulder peaks appeared at the corresponding positions, corresponding to the formation of solvated EC and DEC molecules. The peak shift value of 3M electrolyte is greater than that of 1M electrolyte, indicating that the solvation effect of high concentration electrolyte is stronger. For DME and THF solvents, after adding KFSI, shoulder peaks appeared at 1367 and 1182 cm -1 A peak appears near , which corresponds to the S=O stretching vibration of FSI-. In addition, the shift of the COC peak after adding KFSI is smaller than that after adding KFSI, indicating that the bond energy between THF and KFSI is weaker.

[0088] like Figure 8 As shown in the figure, in high concentration electrolyte, 3M KFSI / THF has the smallest red shift, and 3M KFSI / EC+DEC has the largest red shift. This also indicates that THF has a weak interaction with K+. The solvation structure dominated by CIP and AGG in the THF system means that the coordination ability of K+ and FSI- is strong, while the solvation ability of THF solvent is low. The lower solvation / desolvation ability of THF may induce anion-derived SEI and promote kinetics.

[0089] like Fig. 9 As shown, the F of SEI formed in 3M KFSI / THF - The signal intensity is higher than that of the SEI formed in 3M KFSI / EC+DEC, indicating that a F-rich SEI layer is formed in the 3M KFSI / THF system. - It is evenly distributed in the SEI formed with 3M KFSI / THF as the electrolyte, but unevenly distributed in 3M KFSI / EC+DEC.

[0090] Among the above embodiments, embodiment 4 is the best embodiment.

[0091] Comparative Example 1

[0092] The remaining steps of this comparative example are the same as those of Example 4, except that KFSI is replaced by KTFSI. The results show that the potassium storage capacity and cycle stability are both reduced.

[0093] Comparative Example 2

[0094] The remaining steps of this comparative example are the same as those of Example 4, except that THF is replaced by 2-methyltetrahydrofuran (2MeTHF). It is found that the rate performance is significantly reduced due to the reduction in conductivity.

[0095] Comparative Example 2

[0096] The remaining steps of this comparative example are the same as those of Example 4, except that 3M KFSI / THF is replaced by 5M KFSI / THF. The results show that the rate performance is significantly reduced due to the increase in viscosity.

Claims

1. A potassium ion half-cell, characterized in that: The invention comprises potassium metal, CN-COF material and electrolyte. The CN-COF material is synthesized by heating 1,2,4,5-tetraaminobenzene, cyclohexanone octahydrate, N-methylpyrrolidone and concentrated sulfuric acid in an oil bath, purified and then freeze-dried. The electrolyte is a potassium bis(fluorosulfonyl)imide salt-based electrolyte.

2. A potassium ion half-cell according to claim 1, characterized in that: The solvent of the bis(fluorosulfonyl)imide potassium salt-based electrolyte is one or more of ethylene carbonate, diethyl carbonate, ethylene glycol dimethyl ether and tetrahydrofuran.

3. A potassium ion half-cell according to claim 1, characterized in that: The solvent of the bis(fluorosulfonyl)imide potassium salt-based electrolyte is tetrahydrofuran.

4. A potassium ion half-cell according to claim 1, characterized in that: The concentration of the electrolyte is 1-3 mol / L.

5. A method for preparing a potassium ion half-cell, characterized in that: The following steps are involved: Step 1: In a protective atmosphere, 1,2,4,5-tetraaminobenzene, cyclohexanone octahydrate and N-methylpyrrolidone are placed in an ice bath, concentrated sulfuric acid is added, the temperature is raised to room temperature, and then replaced with an oil bath. After the heating is completed, the mixture is cooled to room temperature and water is added. At this time, a solid product is precipitated, which is collected by filtration, purified, and freeze-dried to obtain a CN-COF material; Step 2, under a protective atmosphere, fully dissolving bis(fluorosulfonyl)imide potassium salt and a solvent to obtain an electrolyte; Step three, assemble the CN-COF material, electrolyte and potassium metal into a potassium ion half-cell.

6. A method for preparing a potassium ion half-cell according to claim 5, characterized in that: In the step 1, the mass volume ratio of 1,2,4,5-tetraaminobenzene, cyclohexanone octahydrate and N-methylpyrrolidone is 2g:2-3g:80mL.

7. The method for preparing a potassium ion half-cell according to claim 5, characterized in that: In the step 1, the temperature of the oil bath is 170-180° C., and the time is 7-9 hours.

8. The method for preparing a potassium ion half-cell according to claim 5, characterized in that: In the step 1, the temperature is raised to room temperature and then kept warm for 2 to 3 hours.

9. The method for preparing a potassium ion half-cell according to claim 5, characterized in that: In the step 2, the concentration of the electrolyte is 1 to 3 mol / L.

10. The method for preparing a potassium ion half-cell according to claim 5, characterized in that: In the step 2, the solvent is one or more of ethylene carbonate, diethyl carbonate, ethylene glycol dimethyl ether, and tetrahydrofuran.